Strong Fermi-level pinning at metal contacts to halide perovskites. Issue 42 (19th October 2021) - Hong, Kootak; Kwon, Ki Chang; Choi, Kyoung Soon; Le, Quyet Van; Kim, Seung Ju; Han, Ji Su; Suh, Jun Min; Kim, Soo Young; Sutter-Fella, Carolin M.; Jang, Ho Won
Abstract : The extrinsic Pb 0 interfacial trap states induce strong Fermi-level pinning at metal/CH3 NH3 PbI3 interfaces. This is due to the interfacial reaction between the deposited metals and iodine from CH3 NH3 PbI3 . Abstract : The performance of halide perovskite-based electronic and optoelectronic devices is often related to interfacial charge transport. To shed light on the underlying physical and chemical properties of CH3 NH3 PbI3 (MAPbI3 ) in direct contact with common electrodes Al, Ti, Cr, Ag, and Au, the evolution of interfacial properties and Fermi level pinning is systematically studied. Given a unique experimental facility, pristine interfaces without any exposure to ambient air were prepared. We observe aggregation of substantial amounts of metallic lead (Pb 0 ) at the metal/MAPbI3 interface, resulting from the interfacial reaction between the deposited metal and iodine ions from MAPbI3 . It is found that the Schottky barrier height at the metal/MAPbI3 interface is independent of the metal work function due to strong Fermi level pinning, possibly due to the metallic Pb 0 aggregates, which act as interfacial trap sites. The charge neutrality level of MAPbI3 is consistent with the energy level of Pb 0 -related defects, indicating that Pb 0 interfacial trap states can be nonradiative recombination sites. This work underlines that control of chemical bonding at interfaces is a key factor for designing future halide perovskite-based devices.